THE DEVELOPMENT OF ANDROID-BASED LEARNING MEDIA APPLICATION FOR BASIC ANALYSIS OF PROSE COURSE - Lina Sholikhatun Maf'Ulah; Rahmah Dewi, Anita (Universitas Islam Lamongan, 2023)
This study aims to elaborate the development of learning media based on android applications and analyze the feasibility of learning media. The design of this study applies Research and Development (R&D) method which uses ADDIE model that was developed by Dick and Carey (1996). Data collection techniques were carried out through interview and questionnaire by validity test data and documentation. The validation of learning media was carried out by media experts and material experts. The media was tested on students in sixth semester of English Education Department at Universitas Billfath. Data analysis techniques uses mixed methods (qualitative and quantitative). The results of this study indicates that the media is suitable for use because it is approved by the media expert validator with a percentage of 85%, the material expert validator 92% and students responses 85%. In addition, this media is able to help students conduct the study more effective, interesting, and fun, and also it helps students get better understanding of Basic Analysis of Prose material. Keywords: Development, Android-based, Learning Media, Prose